2000
DOI: 10.1007/s11940-000-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Parkinson’s disease

Abstract: Depression is very common in Parkinson's disease (PD), but its severity and particular symptoms vary. It can often be difficult to diagnose because many of the symptoms typically associated with depression (eg, sleep difficulties, fatigue) can be seen in nondepressed patients with PD, and signs thought to represent depression (eg, lack of facial expression, slowness) can be produced by PD itself. Apathy, although a possible feature of depression, can exist apart from depression and is often associated with cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
1
7
0
1
Order By: Relevance
“…Furthermore, a number of PD patients who had subthalamic nucleus deep brain stimulation suffered from behavioral side effects including cognitive impairments and depression [51][53]. Treatment with TCAs is restricted by adverse effects, however, TCAs like desipramine are effective in treating depression in PD patients and may even reduce motor symptoms [54]. In this study, we used neurotoxins rotenone and 6-OHDA to induce dopaminergic neuron toxicity that mimics human neurodegenerative disease and neuropathological representative of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of PD patients who had subthalamic nucleus deep brain stimulation suffered from behavioral side effects including cognitive impairments and depression [51][53]. Treatment with TCAs is restricted by adverse effects, however, TCAs like desipramine are effective in treating depression in PD patients and may even reduce motor symptoms [54]. In this study, we used neurotoxins rotenone and 6-OHDA to induce dopaminergic neuron toxicity that mimics human neurodegenerative disease and neuropathological representative of PD.…”
Section: Discussionmentioning
confidence: 99%
“…, 2000). Even though the incidence of depression shows no clear correlation with the severity of motor symptomatology (Richard, 2000), higher depression scores were shown to be associated with advancing disease severity, higher akinesia score and occurrence of falls (Schrag et al. , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown in several studies that a substantial proportion of patients with PD has a less severe form of depression (Tandberg et al. , 1996; Leonard, 1999; Richard, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical profile of executive deficits, apathy and depression in older adults may indicate presence of brain lesions in frontal-subcortical regions from cerebrovascular disease, Alzheimer's disease, Parkinson's disease, head trauma and other frontal-subcortical neuro-degenerative diseases (Starkstein et al, 1993;Marin, 1996;Salloway et al, 1996;Alexopolous et al, 1997;Cummings and Benson, 1998;Levy et al, 1998;Gallarda, 1999;Richard, 2000;Andersson, 1999). Starkstein et al (1993) found that cerebrovascular lesions involving the posterior limb of the internal capsule were most often associated with major depression and apathy in patients with stroke and Marin et al (1994) found an association with left hemisphere stroke suggesting that there may be a vulnerable area of the brain for development of an apathy-depression syndrome.…”
Section: Discussionmentioning
confidence: 99%